Pengaruh Penambahan Kitosan dalam Pembuatan Biodegradable Foam Berbahan Baku Pati - Hendrawati, Nanik; Lestari, Yulia Irna; Wulansari, Putri Anggraini (Jurnal Rekayasa Kimia & Lingkungan, 2017)
Biodegradable foam is an alternative packaging to replace the expanded polystyrene foam packaging currently in use. Starch has been used to produce foam because of its low cost, low density, low toxicity, and biodegradability. Chitosan has been added to improve mechanical properties of product . The effect of variation on chitosan amount and starch types was investigated in this study. The amount of chitosan was varied as 0; 5; 10; 15; 20; 25; and 30 % w/w and starch types were used in this research were cassava, Corn and sago starch. Biodegradable foam was produced by using baking process method, all of material (Starch, Chitosan solution, Magnesium Stearate, Carrageenan, Glyserol, Protein Isolates dan polyvinil alcohol (PVOH) were mixed with kitchen aid mixer. The mixture was poured into mold and heated in an oven at 125 oC for 1 hour. Then, foam was tested for its mechanical properties, water absorption and biodegradability and morphology (SEM). The results show that foam made from sago starch had lower water absortion than those made from cassava and corn starch. While, foam made from cassava starch was more biodegradable than the other foam. Biodegradable foam based sago starch and 30 % w/w of Chitosan adition gave the best performence in tensile stress that is 20 Mpa